Um estudo das relações entre arte e ciência no Renascimento: a visão de Piero della Francesca sobre a perspectiva - Moraes, Vagner Rodrigues de (2014)
The study of the distortions created to represent three-dimensional figures in two-dimensional planes, as in paintings and frescoes, brought up the issue of how such distortions could be reduced from the optical, geometric and physiological points of view. Focusing on perspective as studied during the Renaissance by Piero della Francesca (c.1420 - 1492), this research aims to understand what the author meant by distortion and how he had solved it. Piero della Francesca was a painter and also an art theorist, who promoted changing in aesthetic principles. Besides, he conducted research on pictorial, geometric and architectural issues. Of all the treatises he had wrote, only three are conserved, on perspective (De Prospectiva Pingendi), on geometry (Libellus of Quinque Corporibus Regullaribus) and on arithmetic (Trattado d'Abaco). To achieve such responses we have used as documents, the critical edition made from Nicco-Fasola of De Prospectiva Pingendi and, as a secondary bibliography, books and articles about the society in which such theory was inserted, on the writings of optical and art developed in the fifteenth century, that Piero della Francesca, most likely, had accessed